2019
DOI: 10.1039/c9dt01496a
|View full text |Cite
|
Sign up to set email alerts
|

Dithieno[3,2-b:2′,3′-d]arsole-containing conjugated polymers in organic photovoltaic devices

Abstract: Dithieno[3,2-b:2′,3′-d]arsole containing donor polymers are reported and investigated in organic solar cell devices for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A further set of eight structures that feature As···S contacts between the molecular building blocks that help shape the crystal structure are shown in Figure 11 a–h. The longest and shortest of these are observed in the crystal structures of a polymer containing fused dithieno [3,2- b: 2′,3′- d ]arsole units (4-phenyl-4H-arsolo [3,2- b :4,5- b ’]dithiophene) [ 174 ] and an As 3+ complex of a dialkylthiocarbamate (( N,N -dimethyldithiocarbamato)(toluene-3,4-dithiolato)As) [ 175 ], respectively. The first has r (As···S) = 3.976 Å and ∠C–As···S = 160.1° ( Figure 11 a), and the second, r (As···S) = 2.984 Å and ∠C–As···S = 159.1° ( Figure 11 h).…”
Section: Arsenic In Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further set of eight structures that feature As···S contacts between the molecular building blocks that help shape the crystal structure are shown in Figure 11 a–h. The longest and shortest of these are observed in the crystal structures of a polymer containing fused dithieno [3,2- b: 2′,3′- d ]arsole units (4-phenyl-4H-arsolo [3,2- b :4,5- b ’]dithiophene) [ 174 ] and an As 3+ complex of a dialkylthiocarbamate (( N,N -dimethyldithiocarbamato)(toluene-3,4-dithiolato)As) [ 175 ], respectively. The first has r (As···S) = 3.976 Å and ∠C–As···S = 160.1° ( Figure 11 a), and the second, r (As···S) = 2.984 Å and ∠C–As···S = 159.1° ( Figure 11 h).…”
Section: Arsenic In Crystalsmentioning
confidence: 99%
“… Examples showing the attractive engagement of sulfur as a Lewis base in some molecules with the acidic part of As in interacting molecular entities, contributing to the stability of the crystalline material. ( a ) 4-phenyl-arsolo [3,2- b :4,5- b ’]dithiophene (C 14 H 9 AsS 2 ) [ 174 ]; ( b ) ((cyc-hex) 2 (NCS 2 ) 2 AsI, iodo-bis( N,N’ -bis(cyclohexyl)dithiocarbamato)arsenic(III) [ 177 ]; ( c ) (tBuAs 2 ) 2 (N 2 S), 3,7-di-t-butyl-dithia-tetraazadiarsocine [ 178 ]; ( d ) (Ph 2 As 2 )S, 5,10-epithio-5,10-dihydroarsanthrene [ 179 ]; ( e ) (NH 2 Ph)As(S 2 (CH 2 ) 3 ), 4-(1,3,2-dithiarsinan-2-yl)aniline [ 180 ]; ( f ) PhAs(S 2 (CH 2 ) 3 ) 2-phenyl-1,3,2-dithiarsinane [ 180 ]; ( g ) (NO 2 Ph)As(S 2 (CH 2 ) 3 ), 2-(4-nitrophenyl)-1,3,2-dithiarsinane [ 180 ]; ( h ) Me 2 NC(S)SAs(S 2 (3 S ,4 S -1-MePh)), (N,N-dimethyldithiocarbamato)(toluene-3,4-dithiolato)arsenic(III) [ 175 ]. Bond lengths and angles are shown in Å and degree, respectively.…”
Section: Figures Schemes and Tablementioning
confidence: 99%
“…In contrast to conventional methods, which require volatile and toxic arsenic precursors, efficient synthetic routes using nonvolatile arsenic precursors safely produce various functional organoarsenic compounds. , A practical synthetic route for organoarsenic compounds may facilitate the development of arsenic-containing polymers. Various kinds of π-conjugated units such as arsole, arsaalkene, and triphenylarsine have been introduced into polymer backbones through transition metal-catalyzed polycondensation, electropolymerization, and polymer reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Dithieno­[3,2- b :2′,3′- d ]­arsole (DTA) is a promising π-conjugated unit used for synthesizing functional polymers. Heeney et al and our group separately developed DTA polymers in 2016 . The DTA polymers show intense luminescence, high stability, efficient singlet-oxygen generation, photovoltaic performance, and promising charge carrier mobility. To expand the polymer design for further advancement, the diversity of usable comonomers is fundamentally important. Currently, two types of DTA monomers to which coupling reactions can be applied are known.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Among them, dithieno[3,2- b :2′,3′- d ]arsole (DTA) is a particularly attractive arsole derivative because of the easy synthesis and diverse functions. DTAs 10 and DTA-containing polymers 11,12 show intense emission, oxidation resistance, photosensitizing behavior, etc . It was demonstrated that the substituents on the fused-thiophenes affect the photophysical properties.…”
Section: Introductionmentioning
confidence: 99%